An object-oriented approach to programming logic and design - Farrell, Joyce (Boston, MA : Course Technology/Cengage Learning, 2013)
This text takes a language independent approach to develop a foundation in traditional programming principles and object-oriented concepts before learning the details of a specific programming language. Includes programming exercises in every chapter, with review questions, debugging exercises and case projects.
Previous ed. : 2011.
Includes index.
Keywords: Logic programming; Logic design; Object-oriented programming (Computer science).